Non-destructive models for leaf area estimation in chickpea cultivars (Cicer arietinum L.) - Puntel, Simone; Teixeira Schwab, Natália; Zucuni Pes, Luciano; Alchieri, Douglas Vicente; Bianchi Gatto, Ricardo; Abel Trachta, Mariano (Revista Ceres, 2023)
Chickpea is a winter legume with prospects for worldwide consumption growth, mainly demanded by Asian countries. Thus, studies on its growth, such as the leaf area (LA), are important to determine proper management practices for its cultivation. The objective of this work was to determine a mathematical model able to estimate the leaf area (LA) of chickpea in a non-destructive method. For this, a field experiment was carried out in the county of Santa Maria (RS), with five cultivars available in the national market. Several leaves of each cultivar were collected, and their greatest width (W) and longest length (L) were measured. With the aid of a scanner, these leaves were photocopied, and their LA (cm2) was determined using software. With the power model, models relating to LA and its dimensions were determined. These models were tested using various statistics, with independent data. The results indicate that for the cultivars BRS Aleppo, BRS Kalifa, Jamu, and BRS Toro the best model is LA= 0,0940.(L)1.8483 and for the cultivar BRS Cícero the best model is LA = 0,1092.L2.1815.